TINGKAT KECANDUAN GAME ONLINE PADA REMAJA - Rahman, Irpan Ali; Ariani, Dini; Ulfa, Nurul (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Online games are games that are connected to the internet, one of which is very much in demand from various groups from children, and teenagers, to adults. It has been unfortunate in this case not everyone can control it well so that it can lead to addiction. Teenagers in their teens almost every day play online games with an estimated 10.7 million people or about 10% of the total users aged 12-24 years based on the survey results, Indonesia ranks eighth in the world and the majority of online game users are young teens. This study aims to identify the level of addiction to playing online games in adolescents in Neglasari Village. The research method used is descriptive quantitative with a cross-sectional approach. The population in this study was 6,236 people. samples were taken using the purposive sampling technique. The results showed that the level of online game addiction in the Neglasari village youth was in the medium category. This study concludes that the description of the level of online game addiction in adolescents in the Neglasari village with the longest duration is categorized with the duration of the category of moderate addiction level.